Trajectory of gut microbiota before and after pediatric cardiopulmonary bypass surgery - Yin, Xi; Xiao, Minhua; Sun, Jing; Feng, Jinqing; Xia, Shuliang; Li, Fengxiang; Liu, Xihong; Li, Jia (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundVaried congenital heart disease (CHD) may induce gut microbiota dysbiosis due to intestinal hypoperfusion or/and hypoxemia. Microbiota dysbiosis has been found in preoperative infants and cardiopulmonary bypass (CPB) exacerbated it further. However, the trajectory of gut microbiota from pre- to early post-CPB and one-year later remains unexplored. We examined this trajectory in the two most common CHDs, i.e., left-to-right shunt (ventricular septal defect, VSD) vs. right-to-left shunt (tetralogy of Fallot, TOF).MethodsWe enrolled 13 infants with VSD and 11 with TOF, and collected fecal samples at pre- and early post-CPB. 10 and 12 age- and gender-matched healthy control infants were enrolled respectively. We also enrolled 13 and 9 gender- and CHD diagnosis- and operation-matched one-year post-CPB patients, and 8 age- and gender-matched healthy control children. 16S rRNA sequencing of fecal samples were performed.ResultsCompared to the control groups, both VSD and TOF pre-CPB groups had significantly increased Enterobacteriaceae and Shigella, and decreased Bifidobacterium (Ps ≤ 0.049). No significant change in microbial community diversity was observed between pre- and early post-CPB periods (Ps≥0.227). Compared with early post-CPB, one-year post-CPB groups had significantly increased short-chain fatty acids-producing microbes (Ps ≤ 0.025), and their microbial communities were close to that of the control group (Ps≥0.102). There was no significant difference in microbial communities between VSD and TOF groups in any of 3 periods (Ps≥0.055).ConclusionIn children with VSD or TOF, gut microbiota dysbiosis existed preoperatively and were not significantly altered by CPB. One-year post-CPB, microbiota significantly improved towards normal. Similar microbial communities were found between children with VSD and TOF throughout the perioperative and long-term postoperative periods.